Equipment‐Free Quantitative Readout in Paper‐Based Point‐of‐Care Testing. Issue 4 (14th August 2019) - Li, Zedong; You, Minli; Bai, Yuemeng; Gong, Yan; Xu, Feng
Abstract: Equipment‐free paper‐based devices with quantitative readout have gained considerable interests in recent years, due to the features of remarkable cheapness, prominent portability, and excellent user friendliness. These equipment‐free strategies have been demonstrated to be able to detect a variety of analytes with good performance, such as metal ions, nucleic acids, and cells, thus showing great potential for point‐of‐care testing in resource‐limited settings. In this review, the latest advances of equipment‐free quantitative readout strategies in paper‐based point‐of‐care testing are summarized, including distance‐based strategy, counting‐based strategy, time‐based strategy, and text‐based strategy. Each type of equipment‐free strategy is sequentially introduced and discussed. Finally, conclusions and perspectives are discussed. Abstract : The exploitation of equipment‐free paper‐based analytical devices with quantitative readout capability shows great application prospects in the point‐of‐care testing (POCT) field, especially for resource‐limited settings, due to the advantages of acceptable cost, excellent portability, and favorable user friendliness. This review focuses on the state‐of‐art advances in the development of equipment‐free strategies for paper‐based POCT.